2006
DOI: 10.1007/s10641-006-9084-6
|View full text |Cite
|
Sign up to set email alerts
|

Reef fish community structure on coastal islands of the southeastern Brazil: the influence of exposure and benthic cover

Abstract: Patterns of community structure in the marine environment are strongly influenced by population relationships to biotic and physical gradients. The aim of this work is to explore the relationships of tropical rocky reef fish assemblages to wave exposure and benthic coverage in a gradient of distance from the coast. The study was conducted on the Guarapari Islands, southeastern Brazilian coast. Fish were sampled by underwater visual census (166 transects) and benthic cover was estimated with quadrats (223 repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
166
2
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 172 publications
(187 citation statements)
references
References 38 publications
7
166
2
12
Order By: Relevance
“…La estructura de la comunidad de peces responde a variables bióticas, tales como la abundancia de competidores potenciales (22) y de presas (15). Para el caso actual con la presencia del invasor, luego que Maljkovic et al (23) encontraran en las Bahamas a especies como M. tigris y E. striatus conteniendo como presa al pez león, Mumby et al (24), en la misma región, estudiaron un grupo de meros y chernas tales como E. striatus, M. tigris, M. bonaci, M. venenosa y M. interstitialis, encontrando una reducción lineal de siete veces en la biomasa del pez león en relación con los meros y chernas; por consiguiente, la evidencia sugiere que la depredación por estas especies sí puede cumplir la función de control natural.…”
Section: Discussionunclassified
See 4 more Smart Citations
“…La estructura de la comunidad de peces responde a variables bióticas, tales como la abundancia de competidores potenciales (22) y de presas (15). Para el caso actual con la presencia del invasor, luego que Maljkovic et al (23) encontraran en las Bahamas a especies como M. tigris y E. striatus conteniendo como presa al pez león, Mumby et al (24), en la misma región, estudiaron un grupo de meros y chernas tales como E. striatus, M. tigris, M. bonaci, M. venenosa y M. interstitialis, encontrando una reducción lineal de siete veces en la biomasa del pez león en relación con los meros y chernas; por consiguiente, la evidencia sugiere que la depredación por estas especies sí puede cumplir la función de control natural.…”
Section: Discussionunclassified
“…The structure of the fish community is due to biotic variables such as the abundance of potential competitors (22) and prey (15). In this case, with the presence of the invader, Maljkovic et al (23) found that in the Bahamas M. tigris and E. striatus preyed on the lionfish.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations